New species, Parahelicomyces yunnanensis sp. nov. and Tubeufia nigroseptum sp. nov. from freshwater habitats in Yunnan, China - Li, Long-Li; Shen, Hong-Wei; Bao, Dan-Feng; Lu, Yong-Zhong; Su, Hong-Yan; Luo, Zong-Long (Phytotaxa, 2022)
Diversity of lignicolous freshwater fungi in northwestern Yunnan, China is currently being studied. Four fresh collections of tubeufiaceous taxa were collected and identified. Among of them, Parahelicomyces yunnanensis sp. nov and Tubeufia nigroseptum sp. nov. are introduced as new species based on morphology and molecular phylogenetic analysis of combined ITS, SSU, TEF1-α and RPB2 sequence data. The detailed descriptions and illustrations of the new species are provided, as well as the morphological comparison with similar taxa are discussed. Two strains of Neohelicomyces aquaticus and Tubeufia cylindrothecia are provided.